Workplace pro-environmental behaviors in small and medium-sized enterprises: An employee level analysis - Adeleke Oladapo Banwo; Jianguo Du (Journal of Global Entrepreneurship Research, 2019)
Employees spend much time in the workplace; however, most research have not examined employee's workplace pro-environmental behavior in small and medium-sized enterprises in developing countries. This paper examines the direct and indirect effect of predictor variables on employee's workplace pro-environmental behavior using the comprehensive action determination model. Employees working in small and medium-sized enterprises (n = 296) in three cities in Jiangsu Province, China, were chosen through snowball, convenience sampling, and survey data were obtained via the administration of self-report questionnaires. Principal component analysis with orthogonal rotation (varimax) was used to subject all measures to uni-dimensionality test using an eigenvalue > 1 criterion. Regression analysis, exploratory factor analysis, and structural equation model were used for data reduction and analysis using SPSS version 22. The findings indicate that perceived behavior control, intention to act, sustainable actions, environmental attitude, and social norms had a direct effect while information need, habit strength, and situational conditions had an indirect effect on workplace pro-environmental behavior.
Keywords: 650; China; Comprehensive action determination model; Context; Employees; Jiangsu Province; Small and medium-sized enterprises; Workplace pro-environmental behavior